Cow's milk allergy prevention and treatment by heat‐treated whey—A study in Brown Norway rats. Issue 6 (16th March 2020) - Graversen, Katrine B.; Ballegaard, Anne‐Sofie R.; Kræmer, Louise H.; Hornslet, Sofie E.; Sørensen, Laila V.; Christoffersen, Heidi F.; Jacobsen, Lotte N.; Untersmayr, Eva; Smit, Joost J.; Bøgh, Katrine L.
Abstract: Background: Food processing, including heat‐treatment, can affect protein structure and stability, and consequently affect protein immunogenicity and allergenicity. A few studies have shown that structural changes induced by heat‐treatment impact the intestinal protein uptake and suggest this as a contributing factor for altered allergenicity. Objective: To investigate the impact of heat‐treatment of a whey‐based protein product on allergenicity and tolerogenicity as well as on intestinal uptake in various animal models. Methods: Immunogenicity and sensitizing capacity of the heat‐treated whey product were compared to that of the unmodified product by intraperitoneal and oral exposure studies, while tolerogenic properties were assessed by oral primary prevention and desensitization studies in high‐IgE responder Brown Norway rats. Results: Heat‐treatment of whey induced partial protein denaturation and aggregation, which reduced the intraperitoneal sensitizing capacity but not immunogenicity. In contrast, heat‐treatment did not influence the oral sensitizing capacity, but the heat‐treated whey showed a significantly reduced eliciting capacity compared to unmodified whey upon oral challenge. Heat‐treatment did not reduce the tolerogenic properties of whey, as both products were equally good at preventing sensitization in naïve rats as well as desensitizing already sensitized rats. Results from inhibitory ELISA and immunoblots with sera from sensitized rats demonstrated that heat‐treatment caused an altered protein and epitope reactivity. Protein uptake studies showed that heat‐treatment changed the route of uptake with less whey being absorbed through the epithelium but more into the Peyer's patches. Conclusion and Clinical Relevance: These results support the notion that the physicochemical features of proteins affect their route of uptake and that the route of uptake may affect the protein allergenicity. Furthermore, the study highlights the potential for heat‐treatment in the production of efficient and safe cow's milk protein‐based products for prevention and treatment of cow's milk allergy.